The birth of urban modernity in Gangnam, Seoul. Issue 4 (12th May 2016) - Kim, Jung In
Abstract : This study explores a formative period in the development of Gangnam, an exclusive district south of the Han River that was conceived of and shaped in the context of South Korea's militaristic and capitalist urban culture of the late 1960s. Created in imitation of what was at the time considered to be a highly modern urbanism that had been transplanted not only from the West but also from neighboring countries such as Japan, Hong Kong and Singapore, Gangnam was meant to provide an urban zone that would be secure from the threat of North Korean aggression while simultaneously proclaiming South Korea's ambitions to become a modern nation. This drive to create a new identity for Korea as a capitalist and developed nation, combined with the strong authoritarian nature of the South Korean state, meant that the implementation of modernist architecture and urbanism in Gangnam was primarily made to serve the nation-building and entrepreneurial ambitions of the state. Gangnam thus provides an example of the implementation of modernist structures and planning concepts that were originally envisioned as ways of providing meaningful public space by countering unchecked private speculation (i.e. massive apartment complexes, neighborhood units, superblocks, and automobile-oriented roadways) in the service of materialism at its most flamboyant. This perplexing condition could be said to be the result of what happens when architectural or urban forms are emptied of their publically-oriented ethical impulse, particularly in state-led large-scale urbanisation. While Gangnam can in some respects be considered to be a successful implementation of a modernist cityscape in the sense that it continues to be developed and thrive, it has become the centre of a segregated and unequal urbanity characterized by a highly materialist and extremely competitive culture that is diametrically opposed to the original intentions of those earlier modernist avant-gardes.